2017
DOI: 10.2151/jmsj.2017-010
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Variations in the Boundary Layer Height of Arid and Semiarid Areas in East Asia and North Africa

Abstract: Based on the ERA-20C, climatic variations of the boundary layer height (BLH) over arid and semiarid areas in East Asia and North Africa that span 1900-2010 were analyzed. In East Asia, the BLH exhibited a descending trend from arid region centers to the periphery. Over the past 111 years, the BLH has had a rising trend of 14.0 m decade . in the representative region (NA2) of other regions with the 111-year average of 882 m. In the 1940s and the 1970s, NA1's BLH had two obvious increases that caused the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This is similar to the findings of Zhao et al . (2017a,b) who verified the applicability of the BLH dataset in arid and semi‐arid regions of East Asia by comparing the sounding data with the ERA‐Interim dataset. These indicate that the ERA‐20C data should have good applicability within the study area.…”
Section: Results and Analysismentioning
confidence: 99%
“…This is similar to the findings of Zhao et al . (2017a,b) who verified the applicability of the BLH dataset in arid and semi‐arid regions of East Asia by comparing the sounding data with the ERA‐Interim dataset. These indicate that the ERA‐20C data should have good applicability within the study area.…”
Section: Results and Analysismentioning
confidence: 99%
“…It is shallow at night (<500 m) as a result of surface radiation cooling but deepens during the day (by several kilometres) mainly due to solar heating (Molod et al ., 2015). In addition to surface radiation, the PBLH is also closely related to meteorological factors such as the cloud cover, soil moisture content, wind speed, surface temperature, and specific humidity (Wang and Wang, 2004; Molod et al ., 2015; Zhao et al ., 2017). A further exploration of the relationship between the PBLH and meteorological factors will help us to better understand the evolution of the boundary layer structure and its association with land–atmosphere feedback mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…There are also spatial variations in the correlations between the PBLH and meteorological factors (Seidel et al, 2012;Guo et al, 2016). Based on monthly reanalysis data, Zhao et al (2017) reported that the PBLH trend in East Asia has a stronger correlation with thermodynamic (the surface sensible and latent heat fluxes) than dynamic (wind components and wind shear) factors, whereas in North Africa, the PBLH trend has a stronger correlation with dynamic factors. This partly results from the internal spatial variability of the PBLH (Zhang et al, 2020b), which may be attributed to hydrological factors (Seidel et al, 2012).…”
mentioning
confidence: 99%
“…Gamo (1996) and Zhao et al . (2017) investigated the characteristics of the PBL height in arid/semi‐arid regions, but they did not examine the relationship of the PBL characteristics with the occurrence of dust events.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between the development of convective mixed layers and the occurrence of dust events is not well documented from a statistical point of view. Gamo (1996) and Zhao et al (2017) investigated the characteristics of the PBL height in arid/semi-arid regions, but they did not examine the relationship of the PBL characteristics with the occurrence of dust events.…”
Section: Introductionmentioning
confidence: 99%